2017
DOI: 10.1111/apt.14175
|View full text |Cite
|
Sign up to set email alerts
|

Lack of immunogenicity of hydrolysed wheat flour in patients with coeliac disease after a short‐term oral challenge

Abstract: We confirm that fermentation of wheat flour with sourdough lactobacilli and fungal proteases is capable of abolishing the T cell immunogenicity of gluten in coeliac patients. Our data also validate the short-term oral challenge as a useful tool for testing the efficacy of novel therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
(52 reference statements)
2
20
0
1
Order By: Relevance
“…In line with previous studies, [ 28,34 ] we observed a large individual variability in the level of IFN‐γ production among the CD volunteers. A variable number of IFN‐γ SFC was detected in the PBMCs even before the gluten intake started (day 0).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with previous studies, [ 28,34 ] we observed a large individual variability in the level of IFN‐γ production among the CD volunteers. A variable number of IFN‐γ SFC was detected in the PBMCs even before the gluten intake started (day 0).…”
Section: Discussionsupporting
confidence: 92%
“…In order to address this hypothesis, we further analyzed the capability of TM and TA gluten challenge to mobilize T cells reactive to five immune‐dominant epitopes from α‐ , ω‐ , and γ‐gliadins in a subgroup of CD volunteers. Despite a wide individual variability in the profile of recognized peptides, that is compatible with previous studies, [ 28,34,36 ] overall, we observed that the TM challenge elicited a reduced number of epitope specific T cells. In more details, the patients eating TM bread had a lower frequency of IFN‐γ secreting cells reactive to DQ2.5‐glia α1a/b/α2 epitopes, harbored in the known 33‐mer peptide, in contrast to patients eating TA bread.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…En los IELs, se encuentran tres poblaciones mayoritarias de células: linfocitos con TCR α/β + CD8 + , linfocitos con TCR / + y células NK. Aunque solo en el caso de los linfocitos TCR α/β + CD8 + pudo observarse una respuesta específica (Mandile et al 2017;Mazzarella et al 2008). En conjunto, estas células son activadas por IFNs tipo I e IFN, reconocen señales de estrés celular expresadas por los enterocitos y son inductores de apoptosis de enterocitos (Olaussen et al 2002).…”
Section: Mecanismos De Muerte Celular Asociados a Enfermedad Celíacaunclassified